PERLINDUNGAN HUKUM BAGI MASYARAKAT TERHADAP PENGELOLAAN LIMBAH RUMAH POTONG HEWAN DI INDONESIA - Irnawati; Rhenny Ratnawati (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2019)
The purpose of writing this article is to understand the legal protection for people against the management of slaughterhouse waste in Indonesia. Animal slaughterhouse management waste is waste resulting from the cutting process and if not managed properly will have an impact on the surrounding environment. Pollution of animal slaughterhouse waste management can occur if not properly managed. The method of approaching research is normative juridical. The results of the study provide an answer that the protection of the law against the community is a fundamental thing to be accommodated by the surrounding government. Waste management is an absolute thing done by the state to ensure the good survival of the people in Indonesia. Keywords : legal protection, community, waste management, slaughterhouse